2016
DOI: 10.4028/www.scientific.net/kem.706.78
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Wood-Based Composites Based on Biodegradable Polymer

Abstract: The article presents the wood composite materials based on biodegradable component of polyvinyl acetate with the filler in a form of wood flour of pine trees of two types: unmodified and thermally modified pine. The sorption properties of composite of both species, namely the ability of a material to absorb moisture depending on the quantity and nature of wood filler were studied. The strength characteristics of composite materials with non-modified and modified wood fillers were investigated and revealed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For comparison, Chen et al [ 22 ] studied a composite of PVAc and natural rice husk fibers and reported a similar tensile strength of 8.34 MPa for the best formulation (50:50). Safin et al [ 48 ] evaluated composites of PVAc and natural pine wood fibers and found tensile strength of 19 and 12 MPa, for 10% or 50% of fibers, respectively, that is, a decreasing trend with increasing wood content. A decrease in strength of composites with higher filler content is partly justified by the greater interaction among fibers, increasing their effective diameter and reducing the aspect ratio at very high contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, Chen et al [ 22 ] studied a composite of PVAc and natural rice husk fibers and reported a similar tensile strength of 8.34 MPa for the best formulation (50:50). Safin et al [ 48 ] evaluated composites of PVAc and natural pine wood fibers and found tensile strength of 19 and 12 MPa, for 10% or 50% of fibers, respectively, that is, a decreasing trend with increasing wood content. A decrease in strength of composites with higher filler content is partly justified by the greater interaction among fibers, increasing their effective diameter and reducing the aspect ratio at very high contents.…”
Section: Resultsmentioning
confidence: 99%
“…The PVAc/PFW 5%-20% samples were within 65%-70%, all higher than the sample without PFW (≈52%), an increase of around 36%. For comparison, Laftah and Wan Abdul Rahman [41] reported 1.3% moisture absorption for a composite with 20:80 rice husk:rice bran, with 30 parts of PVAc resin, and Safin et al [48] reported 10% moisture absorption for a composite with PVAc and natural pine wood fibers (50:50). These values are much lower than the 183% absorption reported by Castro [49] for wet blue leather residues, which are similar to the leather residues used in the current work.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, structures made of wood composites are gaining in more popularity in the construction industry [1][2][3][4]. Composites are widely used in construction due to the advantages of the cast-in-place composition obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were carried out to get wood-filled composite materials based on PLA and wood flour subjected to preliminary thermal treatment at high temperatures without oxygen access [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%